EDUKASI KESELAMATAN PERKERETAAPIAN SEJAK DINI KEPADA MURID TK DAN SD DI TULUNGAGUNG - Puspitasari, Mariana Diah; Aghastya, Adya; Iswanto, Ary Putra; Wicaksono, Adi (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
Safety is still the main menu in the implementation of transportation in Indonesia. It is the 11th goal of the Sustainable Development Goals (SDGs). In reality, this safety has not been fully achieved. Accidents still occur frequently in air, sea, land and rail transportation modes. Accidents at railroad crossings are still common, even involving young children. To mitigate this, the government is making efforts to improve safety at level crossings with several approaches, one of which is infrastructure development. This must also be supported by awareness and understanding of safety in transportation, especially trains. Not all people understand how to act safely at the station, inside the train, and at the crossing. For this reason, a comprehensive socialization of the railway safety campaign is needed to all levels of society. From the findings in the field, the understanding of teachers and kindergarten and elementary school students participating in education on railway safety both at the station, inside the train, and at level crossings based on the pre-test results is not too broad. Elementary school teachers had the highest average score of 60. In contrast, kindergarten students had the lowest average score of 12.72. In fact, many kindergarten children have never ridden a train. In addition, the impact of education on children's understanding of railroad safety both at the station, in the train, and at level crossings is very significant. The results of testing the difference in the average pre-test and post-test scores of participants with a paired T test showed that the test scores were different before and after education. So it can be concluded that education has an impact on the level of understanding of the participants.